What's Our Position? A Critical Media Literacy Study of Popular Culture Websites With Eighth-Grade Special Education Students. Issue 1 (2nd January 2016) - Kesler, Ted; Tinio, Pablo P. L.; Nolan, Brian T.
Abstract : This article reports on an action research project with 9 eighth-grade special education students in a self-contained classroom in an urban public school. The 1st author, in collaboration with the classroom teacher (3rd author), taught the students a critical media literacy framework to explore popular culture websites. Students learned to analyze these sites for issues of authorship; design; intended audience; ideology; and political, social, and profit motive agendas. Based in theories from new literacies, multiliteracies, multimodal literacy, and critical media literacy, the article addresses the following questions: What understandings as critical readers of popular culture websites did the students exhibit? How did these understandings contribute to their development as 21st-century literate people? Through the use of screen capture software and think-aloud protocol, we were able to recreate each student's reading process. Students then created alternative media productions using Glogster. We analyzed each student's glog using the grammar of visual design. Analysis revealed students' critical media literacy understandings. We present 3 themes in the findings: inferential thinking, a dialectic across multiple literacies, and multimodal expression. We present 2 telling cases to articulate our analysis and the dimensions of each theme. The article concludes with implications for future research, policy, and pedagogy, particularly in critical media literacy with special education populations.